Digital Village Governance in Digital Gap Mitigation in the Indonesian Smart Village Era 2025 - Andhika, Hagi (Politeknik Siber Cerdika Internasional, 2025)
Indonesia's Smart Village Program 2025 targets digitalization of 75,265 villages, yet only 3,000 have successfully transformed by 2024, while digital divide continues widening between technologically advanced and lagging villages. This study analyzes digital village governance practices, identifying effective mechanisms for mitigating digital divide across Indonesian villages. Using explanatory sequential mixed-method, data were collected from 60 villages (30 advanced, 30 lagging) across three regions, involving 660 respondents and 30 key informants. Quantitative analysis employed multiple linear regression (SPSS), while qualitative data utilized thematic analysis (NVivo). Four governance typologies emerged Hybrid Collaborative (8.4±0.6), Technology-Centric (7.4±0.8), State-Centric Transitional (5.1±0.7), and Community-Driven Minimalist (3.3±0.9) demonstrating 5.1-point heterogeneity. Four governance dimensions institutional capacity (β=0.412), multi-stakeholder collaboration (β=0.378), community participation (β=0.351), and transparency-accountability (β=0.289) explain 73.4% of digital divide variance (R²=0.734, p<0.001). Notably, 40% of lagging villages developed adaptive innovations including offline-digital hybrid governance, achieving 4.5 times higher governance improvement. Implications findings necessitate reorienting from